Global and regional estimates of clinical and economic burden of low back pain in high-income countries: a systematic review and meta-analysis - Fatoye, Francis; Gebrye, Tadesse; Ryan, Cormac G.; Useh, Ushotanefe; Mbada, Chidozie (Frontiers in Public Health, 2023)
Background: Low back pain (LBP) is a common health problem, and the leading cause of activity limitation and work absence among people of all ages and socioeconomic strata. This study aimed to analyse the clinical and economic burden of LBP in high income countries (HICs) via systematic review and meta-analysis. Methods: A literature search was carried out on PubMed, Medline, CINAHL, PsycINFO, AMED, and Scopus databases was from inception to March 15th, 2023. Studies that assessed the clinical and economic burden of LBP in HICs and published in English language were reviewed. The methodological quality of the included studies was assessed using the Newcastle–Ottawa quality assessment scale (NOS) for cohort studies. Two reviewers, using a predefined data extraction form, independently extracted data. Meta-analyses were conducted for clinical and economic outcomes. Results: The search identified 4081 potentially relevant articles. Twenty-one studies that met the eligibility criteria were included and reviewed in this systematic review and meta-analysis. The included studies were from the regions of America (n = 5); Europe (n = 12), and the Western Pacific (n = 4). The average annual direct and indirect costs estimate per population for LBP ranged from € 2.3 billion to € 2.6 billion; and € 0.24 billion to 8.15 billion, respectively. In the random effects meta-analysis, the pooled annual rate of hospitalisation for LBP was 3.2% (95% confidence interval 0.6% - 5.7%). The pooled direct costs and total costs of LBP per patients were USD 9231 (95% confidence interval -7126.71 - 25588.9) and USD 10143.1 (95% confidence interval 6083.59 - 14202.6), respectively. Conclusion: Low back pain led to high clinical and economic burden in HIcs that varied significantly across the geographical contexts. The results of our analysis can be used by clinicians, and policymakers to better allocate resources for prevention and management strategies for LBP to improve health outcomes and reduce the substantial burden associated with the condition.